Shaping individual preferences for social protection: The case of platform workers - Francesco Bogliacino; Valeria Cirillo; Cristiano Codagnone; Marta Fana; Francisco Lupiá\~nez-Villanueva; Giuseppe A. Veltri (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
Workers who perform their occupations through platforms are becoming an increasing share of the labour force. The debate is polarized between those arguing for platforms as an instrument to increase flexibility and labor force participation, and those who see it as a further mechanism to increase Non Standard Work (NSW). This debate is policy relevant because in either case, platform participation is associated to a difference in terms of willingness to contribute to the social security system. Nevertheless, the evidence is scant because we lack reliable data sources. In this contribution, we use a dedicated survey to estimate Willingness to Pay (WTP) for social security and estimate the causal impact of platform participation using a selection on observable strategy. We found that platform workers are less disposed to contribute to social security, although perception of accessibility and adequacy are not affected. Results are robust to specifications and multiple hypotheses testing.
Keywords: J32; J40; C21; 330; employment; preferences; work; economic behavior